A helping hand: artificial nest site provisioning increases breeding success of a tropical seabird. Issue 2 (19th August 2016) - Hart, LA; Gane, J; Olivier, I; Downs, CT; Brown, M
Abstract : Common white terns Gygis alba lay a single egg balanced on rocks or branches and consequently are at risk of low nesting success. A novel technique of hollowing out coconut husks and providing artificial nest sites was developed on Cousine Island, Seychelles. Our study aimed to critically assess whether common white tern nesting success differed between artificial and natural nest sites. For natural nest sites, nesting success and the stage of nest failure were also compared between seasons, nest heights, and tree species. Finally, we compared results from our study to those of a study conducted 10 years ago on the same island. Nesting success differed significantly between artificial nests and natural nests, with the success of artificial nests nearly double that of natural nests. Hatching success was similar for artificial and natural nests (65% and 52% respectively), suggesting coconut husks do not reduce egg losses, but rather provide secure perches for young chicks. Most natural nest failures occurred during the egg phase (70%), followed by the youngest chick phase (21%). Of the eggs that hatched in natural nests, 61% fledged successfully. Tree species and season significantly influenced nesting success for natural nests and nest height varied significantly between tree species. Higher nesting success was observed during the mixed seasonal period (50%) followed by the cooler, windier and drier South-East Monsoon season (33%). The hotter and more humid North-West Monsoon period had the lowest nesting success (20%). Comparisons of nesting success at natural and artificial nest sites with the earlier study did not differ significantly, despite a smaller population of common white terns being present on the island at that stage. Our results support the use of artificial nest sites to improve nesting success for this species and serve as a model for similar species currently under threat.